Spectroscopia FTIR a diferitelor esenţe de lemn utilizate ca suport în pictura pe lemn - Măruțoiu, Constantin (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
This paper investigates different wood essences used for the construction of churches, icons and other church objects with the help of non-destructive FTIR spectroscopy. Non-destructive FTIR (Fourier-transform infrared) reflectance spectroscopy is a fast method used to establish the wood species material which a work of art is made of (construction, statue, religious object, etc.) for restoration purposes. By comparing the obtained spectra with standards we can accurately determine the object nature. This method provides a “fingerprint” of the entire chemical composition and the ratio of the sample compounds. FTIR reflectance spectroscopy was performed using a tripod mounted Bruker Alpha II device with a contactless forward-looking reflection unit specialized for paintings, spectral domain 400-4000 cm-1, resolution 2 cm-1, OPUS /IR software in Windows 10.